Development of a Brand Polarization Scale in Sports - Saglik, Ugur; Gulmez, Yavuz Selim (International Review of Management and Marketing, 2026)
The aim of this study is to explain the phenomenon of brand polarization in the context of the sports industry and to develop a valid and reliable scale to measure this phenomenon. Although polarization has been examined across various disciplines in the literature, the lack of a systematic measurement tool in the context of sports marketing and football fandom is noteworthy. In this study, the concepts of polarization, brand, and brand polarization were first examined theoretically, followed by an analysis of the transformation of the sports industry, the globalization of football, and fan behavior. Based on this theoretical foundation, scale items were developed and refined through expert opinions, a pilot study, and data collected from the sample. The validity and reliability of the scale were tested using Cronbach’s Alpha, KMO, Bartlett’s Test, Exploratory Factor Analysis, and Confirmatory Factor Analysis. The findings indicate that the scale demonstrates high internal consistency and a robust factor structure. Data were collected through snowball and convenience sampling methods and tested across different demographic groups. The analyses revealed two dimensions: the positive pole, reflecting fans’ strong positive attitudes toward their supported teams, and the negative pole, representing their strong negative attitudes toward rival teams. In conclusion, the developed scale provides an original theoretical contribution to the fields of international business, international marketing, and sports literature, while also serving as a practical tool applicable across all sports disciplines.